Extra View: Sirt1 Acts As A Gatekeeper Of Replication Initiation To Preserve Genomic Stability. (1st January 2018) - Utani, Koichi; Aladjem, Mirit I.
Abstract: Since the discovery of a yeast gene silencing modifier (Silent Information Modifier 2, SIR2) and its role in maintaining genomic stability more than two decades ago, SIR2 homologs (sirtuins) were identified in diverse species. Sirtuins are protein deacetylases that play diverse roles in proper cellular metabolism including cell cycle progression and maintenance of genomic stability. In yeast, SIR2 interacts with replication origins and protein complexes that affect both replication origin usage and gene silencing. In metazoans, the largest SIR2 homolog, SIRT1, is implicated in epigenetic modifications, circadian signaling, DNA recombination and DNA repair. Until recently, very few studies investigated the role of mammalian SIRT1 in modulating DNA replication. We discuss a newly characterized interaction between human SIRT1 and the DNA replication machinery, reviewing data from recent studies that have investigated how complex signaling pathways that involve SIRT1 affect cellular growth regulatory circuits.